Association between tissue inhibitor of metalloproteinase (TIMP) genetic polymorphisms and primary ovarian insufficiency (POI) - An, Hui Jeong; Ahn, Eun Hee; Kim, Jung Oh; Park, Han Sung; Ryu, Chang Soo; Cho, Sung Hwan; Kim, Ji Hyang; Lee, Woo Sik; Kim, Nam Keun (Maturitas, 2019)
•We investigated the association between six tissue inhibitor of metalloproteinase (TIMP) polymorphisms and primary ovarian insufficiency in Korean females.•The TIMP2G > C (rs8179090) and TIMP2G > A (rs2277698) genotypes were strongly associated with primary ovarian insufficiency.•Our data suggest that the TIMP2 genotypes and TIMP1 haplotypes may increase the risk of primary ovarian insufficiency in Korean women. Until now, an association between tissue inhibitor of metalloproteinase (TIMP) polymorphisms and primary ovarian insufficiency (POI) has not been identified. The aim of our study was to investigate whether the TIMP polymorphisms TIMP1T > C (rs4898), TIMP1G > A (rs6609533), TIMP2G > C (rs8179090), TIMP2G > A (rs2277698), TIMP3G > A (rs135029), and TIMP4T > C (rs3755724), which regulate matrix metalloproteinases (MMPs), confer a risk for primary ovarian insufficiency (POI) in Korean women (further studies would be required to evaluate the associations between TIMP polymorphisms and POI in other populations). We genotyped 137 POI patients and 236 controls for the single nucleotide polymorphism sites using PCR–RFLP analysis. Differences in the frequencies of the TIMP1T > C (rs4898), TIMP1G > A (rs6609533), TIMP2G > C (rs8179090), TIMP2G > A (rs2277698), TIMP3G > A (rs135029), and TIMP4T > C (rs3755724) genotypes between patients and controls were compared, and odds ratios and 95% confidence intervals were determined to measure of the strength of the association between the genotypes and POI. The TIMP1T > C (rs4898), TIMP1G > A (rs6609533), TIMP2G > C (rs8179090), TIMP2G > A (rs2277698), TIMP3G > A (rs135029), and TIMP4T > C (rs3755724) genotypes, but especially the TIMP2 genotypes, were found more frequently in POI patients than in control subjects. Among the four TIMP loci, the TIMP1T > C (rs4898), TIMP1G > A (rs6609533), TIMP2G > C (rs8179090), TIMP2G > A (rs2277698), TIMP3G > A (rs135029), and TIMP4T > C (rs3755724) haplotypes were identified more frequently in POI patients than in control subjects and conferred susceptibility to POI (P <0.0001). The TIMP2G > C (rs8179090) and G > A (rs2277698) alleles were strongly associated with POI. Our data suggest that the minor TIMP2 alleles may increase POI risk in Korean women.